Coronary Thrombosis and the Platelet Glycoprotein IIIA Gene PLA2 Polymorphism - Durante-Mangoni, Emanuele; Davies, Graham J.; Ahmed, Nabeel; Ruggiero, Giuseppe; Tuddenham, Edward G. (Thrombosis and Haemostasis, 1998)
Myocardial infarction results from a platelet-rich occlusive coronary thrombus. Platelet membrane glycoprotein IIb/IIIa plays an important role in platelet adhesion and aggregation. Two polymorphisms of the gene encoding the IIIa subunit, PLA1 and PLA2, have been identified. We investigated the frequency of these polymorphisms in 114 consecutive patients with a history of angina-like chest pain admitted for coronary arteriography. Forty-three of these patients had previously suffered a myocardial infarction. The PLA2 polymorphism was found in 21% of the patients with previous myocardial infarction and in 27% of the patients with angina-like chest pain but no previous myocardial infarction (p = 0.634). There was also no significant association with the extent of coronary disease. There is no evidence, therefore, from this study of an association between the PLA polymorphisms and the occurrence of myocardial infarction.